(untitled) (Scientific journal of the Fergana State University, 2024)
The samples that were obtained by experimental means are the subject of this paper. Information was supplied regarding their composition, drying processes, and technologies that were investigated. In our country, there is a steady demand for dried fruits, vegetables, and medicinal plants. In order to meet this demand, the biological ingredients that are useful in dried items, as well as the methods that are used to package them, were investigated.